2018
DOI: 10.1177/0018720818816261
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Strategies for Reducing Upper Extremity Physical Exposure Associated With Floor Mopping: A Systematic Review

Abstract: Objective: This systematic review synthesizes literature on upper extremity physical exposure associated with floor mopping, in order to (a) assess the impact of changes in mopping systems on physical exposure and (b) propose recommendations for strategies to reduce exposure. Background: Floor-cleaning tools and equipment have undergone major improvements. Existing studies have focused on mop design modifications and cleaning efficiency. However, less is known about strain responses caused by modern tools an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…Discrepancies were discussed and resolved. This approach matches methods used previously (e.g., Kazi et al, in press; Patterson, 2018; Wallius et al, 2019).…”
Section: Methodssupporting
confidence: 61%
“…Discrepancies were discussed and resolved. This approach matches methods used previously (e.g., Kazi et al, in press; Patterson, 2018; Wallius et al, 2019).…”
Section: Methodssupporting
confidence: 61%
“…Shoulder muscle activity in the right/dominant side of subjects was found to be significantly lower when the adjustable handle was used. Finally, Wallius and colleagues [ 22 ] reviewed several floor mopping studies and categorized the findings by level of evidence to support interventions to reduce job task physical exposure. The authors concluded there to be “moderate evidence” that mop handle designs can have a positive impact on reducing such exposures and are “a practice to be considered”.…”
Section: Introductionmentioning
confidence: 99%